2020
DOI: 10.1111/jfb.14253
|View full text |Cite
|
Sign up to set email alerts
|

Native bighead carp Hypophthalmichthys nobilis and silver carp Hypophthalmichthys molitrix populations in the Pearl River are threatened by Yangtze River introductions as revealed by mitochondrial DNA

Abstract: Bighead carp Hypophthalmichthys nobilis and silver carp Hypophthalmichthys molitrix have been two economically important aquaculture species in China for centuries. In the past decades, bighead and silver carp have been introduced from the Yangtze River to many river systems in China, including the Pearl River, in annual, large‐scale, stocking activities to enhance wild fisheries. Nonetheless, few studies have assessed the ecological or genetic impacts of such introductions on native conspecific fish populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Previous studies have reported that grass carp in the Yangtze River had two mtDNA lineages (Lu et al, 1997;Zhao et al, 2011;Zhai et al, 2020). This finding is consistent with those reported for bighead carp Hypophthalmichthys nobilis and silver carp Hypophthalmichthys molitrix in the Pearl River, both of which also present two mtDNA lineages in the Pearl River (Li et al, 2020). However, a larger divergence was detected in bighead carp and silver carp than that in grass carp, suggesting that two Hypophthalmichthys species likely underwent a more complex evolutionary history.…”
Section: Genetic Diversity and Genetic Structuresupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies have reported that grass carp in the Yangtze River had two mtDNA lineages (Lu et al, 1997;Zhao et al, 2011;Zhai et al, 2020). This finding is consistent with those reported for bighead carp Hypophthalmichthys nobilis and silver carp Hypophthalmichthys molitrix in the Pearl River, both of which also present two mtDNA lineages in the Pearl River (Li et al, 2020). However, a larger divergence was detected in bighead carp and silver carp than that in grass carp, suggesting that two Hypophthalmichthys species likely underwent a more complex evolutionary history.…”
Section: Genetic Diversity and Genetic Structuresupporting
confidence: 91%
“…Human introduction of grass carp from the Yangtze River brought novel genetic resources into the Pearl River and thus elevated the nucleotide diversity of the Pearl River. This pattern was also seen in bighead carp and silver carp (Li et al, 2020). Furthermore, our study indicated that the nucleotide diversity of grass carp was much lower than that of other native carp species such as bighead carp and silver carp, which was also demonstrated in a previous study (Lu et al, 1997).…”
Section: Potential Effects Of Anthropogenic Introduction On the Pearl...supporting
confidence: 87%
“…To conserve wild native common carp, it is necessary to establish a scientific and systematic management system for artificial fish propagation and release (Wang et al ., 2017; Zhang et al ., 2020). Stocking should also use native species, and the release of hybrids and gene‐modified species should be prohibited (Kang et al ., 2017; Li et al ., 2020; Wang et al ., 2015). Although both native Pearl River and Hainan Island common carp populations are referable to C. c. rubrofuscus , they should be managed separately because of their high genetic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Transportation of fish fry from the Perl River Basin and the Yangtze River Basin to other regions is a common practice . A recent mtDNA study on bighead carp and silver carp in the Pearl River revealed the Pearl populations were dominated by genetic material from the Yangtze River, which calls for ceasing the stocking practice of Yangtze fingerlings in the Pearl River to preserve native genetic diversity (Li et al, 2020).…”
Section: G Ene Ti C Variati On and D Iver S It Y Of B I G He Aded Cmentioning
confidence: 99%